Building a Mobile Stroke Unit Based on 5G Technology – A Study Protocol - Gu, Gangfeng; Jiang, Junyao; Zheng, Bo; Du, Xiao; Huang, Ke; Yue, Qinfang; Wang, Jian (Frontiers in Physiology, 2021)
Background: In-time treatment of acute stroke is critical to saving peo-ple’s lives and improving the quality of post-stroke life. A Mobile Stroke Unit (MSU) with 5th generation mobile networks (5G) strengthens the in-teraction of patient information and healthcare resources, thereby reduc-ing response times and improving thrombolysis results. However, clinical evidence of better outcomes compared to regular care is still lacking. Method and Design: In this randomized controlled trial, 484 patients with acute stroke are allocated into the MSU and regular care groups. We es-tablish medical records for each patient and conduct a follow-up of 90 days. The primary outcomes are functional results as defined by utility-weighted modified Rankin Scale (uw-mRS) 90 days after the incidence occurred. Whereas secondary outcomes include the alarm to CT scan completed time, the alarm to treatment decision time, the alarm to thrombolytic time, quality of life, and symptomatic intracranial hemor-rhage combined with NIHSS score as well as cost-effectiveness. Discussion: This study establishes an innovative MSU (based on 5G) to manage acute stroke, comparing its clinical and economic outcomes to regular care and informing decision-makers of the effectiveness of stroke emergency system.